Al-Imām al-Dimiāti's Approach to Basmalah in his book Ithāf Fudalāa al-Bashar bil Qirāaāt al-Arba’a ‘Ashar (Upholding the Virtues of Human Beings with the Fourteen Readings) (Journal of Humanitarian and Applied Sciences, 2021)
The current paper examines al-Imām al-Dimiāti's approach in the Basmalah chapter in his book entitled Ithāf Fudalāa al-Bashar bil Qirāaāt al-Arba’a ‘Ashar (Upholding the Virtues of Human Beings with the Fourteen Readings). This research presents a brief review of al-Imām al-Dimiāti's life and demonstrates his approach to the Basmalah, its related aspects, and the most significant findings. The study also attempts to outline the intellectual as well vocational biography of al-Imām al-Dimiāti, and highlight his contributions to the propagation of the science of Qurʿānic readings at the level of education and authorship. The research followed the inductive approach to extrapolate all the interpretations of al-Imām al-Dimiāti in the Basmalah chapter. The study concluded that al-Imām al-Dimiāti’s book entitled Ithāf Fudalāa al-Bashar bil Qirāaāt al-Arba’a ‘Ashar is one of the most authoritative books authored in his time, and that the Basmalah between two Quranic verses (surah) is mandatory for those who read with affirmation from reciters.
Keywords: approach; al-Imām al-Dimiāti; al-Basmalah; the book of Ithāf Fudalāa al-Bashar bil Qirāaāt al-Arba’a ‘Ashar